Insights Into the Emerging Entity of HER2-Low Breast Cancer - Georges El Haddad; Ernest Diab; Michel Hajjar; Maroun Aoun; Farid Mallat; Ziad Zalaquett; Hampig-Raphael Kourie (International Journal of Breast Cancer)
Human epidermal growth factor receptor 2 (HER2)-low breast cancer (BC) is a subtype of BC that has been recently recognized as a separate clinical entity with distinct clinical and molecular characteristics. It is defined by a low level of HER2 protein expression, which distinguishes it from other more aggressive BC subtypes. Early studies suggest that it may have a more favorable prognosis than HER2-positive BC, as it is less likely to spread to other parts of the body and may be more responsive to standard BC treatments such as chemotherapy, radiation therapy, and hormone therapy. Given the relative new emergence of HER2-low BC, there is still much to be learned about this subtype; ongoing research is focused on identifying the underlying genetic mutations that contribute to HER2-low BC as well as developing targeted therapies that can improve outcomes for patients with this disease. This review is aimed at summarizing the current clinical knowledge on HER2-low BC, with the aim of creating a better understanding of this entity and paving the way for potential interventions and a new standard of care.